TELEMEDICINE IN PRIMARY HEALTH CARE: EVIDENCE, CHALLENGES, AND FUTURE DIRECTIONS IN CHRONIC DISEASE MANAGEMENT - Filip Lachowski,; Ewa Lachowska,; Karolina Wojdat-Krupa,; Karol Sikora,; Maciej Gancarczyk,; Sabina Ściążko-Gancarczyk,; Natalia Domańska,; Sonia Pawełkiewicz,; Olga Łopatko, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Telemedicine has emerged as a pivotal component of modern primary health care (PHC), particularly in the management of chronic diseases such as hypertension, type 2 diabetes, asthma, COPD, and mental health disorders. The increasing prevalence of multimorbidity, combined with limited health system capacity, has accelerated the adoption of digital solutions capable of improving access, continuity, and clinical decision-making. Evidence accumulated during and after the COVID-19 pandemic demonstrates that remote monitoring and digital communication tools enhance patient engagement, support self-management, and enable earlier identification of clinical deterioration.Methods: This review synthesizes findings from randomized controlled trials, systematic reviews, meta-analyses, cohort studies, and implementation research evaluating the role of telemedicine in PHC. The analysis focuses on clinical outcomes, patient-reported measures, system efficiency indicators, and the feasibility of integrating telemedicine into existing organizational structures. Special attention is given to chronic disease management, digital health literacy, algorithmic monitoring, and barriers related to interoperability, equity, and data security.Results and Conclusions: Across 79 empirical studies, telemedicine consistently improves clinical control of chronic conditions, reduces avoidable hospitalizations, strengthens continuity of care, and enhances patient satisfaction. Remote monitoring of blood pressure and glycemic trends demonstrates significant improvements in disease stability, while telepsychiatry expands access to mental health services. Despite its demonstrated effectiveness, full integration of telemedicine requires investment in digital infrastructure, workforce training, and robust cybersecurity protocols. Overall, telemedicine should be regarded not as an adjunct, but as a fundamental pillar of future PHC systems.